2019
DOI: 10.18517/ijaseit.9.1.6385
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Information Quality in the Malaysian Public Sector

Abstract: Information is an important asset that can determine the success or failure of an organization. Hence, the quality of information should not be compromised, instead, it should be an organization's priority. Information should be managed efficiently and effectively to ensure its availability whenever needed, especially for making decisions. Without information quality management, an organization may be seemed unaccountable, holds no integrity, not transparent and competent, thus affecting performance. Most orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This research aims to address a significant gap in understanding the motivational factors that influence Malaysian youth to attend badminton matches. Despite badminton's prominence in Malaysian sports culture and its potential to drive sport tourism, there is a notable lack of empirical research on what motivates youth to attend these events (Hassan & Ahmad, 2019). Government initiatives, such as the "one student, one sport" policy, aim to promote sports participation among students, potentially influencing attendance at sporting events (Ministry of Education Malaysia, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
“…This research aims to address a significant gap in understanding the motivational factors that influence Malaysian youth to attend badminton matches. Despite badminton's prominence in Malaysian sports culture and its potential to drive sport tourism, there is a notable lack of empirical research on what motivates youth to attend these events (Hassan & Ahmad, 2019). Government initiatives, such as the "one student, one sport" policy, aim to promote sports participation among students, potentially influencing attendance at sporting events (Ministry of Education Malaysia, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
“…Additionally, skill waste is about not using people's full abilities or giving them the wrong work or tasks that can cause a delay in the work process. It is due to the employees' lack of competency and experience to execute the tasks [16]. It is undeniable that mistakes from the employees caused high lead time.…”
Section: Public Sector Performances: the Current Issuesmentioning
confidence: 99%
“…However, certain steps must be taken to guarantee that the system's implementation meets the government's goals. Past research by Hassan et al (2019); Hawash et al (2020) found that electronic document management systems are not widely implemented, resulting in several issues in storing and processing all data in enterprises. One of the reasons for failure is a lack of a proper system that fulfils ISO criteria, resulting in noncompliance with the records management concept and policy.…”
Section: Problem Statementmentioning
confidence: 99%
“…According to Ab Aziz et al (2018), an ERM solution becomes a tool in creating and assessing the electronic record-keeping system, demonstrating the value of storage. As it comes together in one solution, the ERM solution incorporates the component or function of the electronic record-keeping system (Hassan et al, 2019). Each organisation's policy or business rule determines how the solution is designed and implemented.…”
Section: Literature Reviewmentioning
confidence: 99%